Extension and Community Resilience: Improving Community Disaster Preparedness Using Online Resources - Emily Ott; Paul Monaghan; Timothy Fogarty (EDIS, 2014)
As Extension agents work to improve the quality of life in their communities, they must increase the capacity to respond to disasters, especially in high risk areas (which includes most of coastal Florida). Community Resiliency is a community’s ability to quickly recover from adversity and it can be enhanced through planning and adaptation using easily available online resources. This 4-page fact sheet describes supplemental educational materials that can be added to community resiliency training, offering background information and specific tools for disaster preparation. Written by Emily Ott, Paul Monaghan, and Timothy Fogarty, and published by the UF Department of Agricultural Education and Communication, October 2014. (UF/IFAS photo by Milt Putnam)